2017
DOI: 10.5194/dwes-10-61-2017
|View full text |Cite
|
Sign up to set email alerts
|

Online total organic carbon (TOC) monitoring for water and wastewater treatment plants processes and operations optimization

Abstract: Abstract.Organic measurements, such as biological oxygen demand (BOD) and chemical oxygen demand (COD) were developed decades ago in order to measure organics in water. Today, these time-consuming measurements are still used as parameters to check the water treatment quality; however, the time required to generate a result, ranging from hours to days, does not allow COD or BOD to be useful process control parameters -see (1) Standard Method 5210 B; 5-day BOD Test, 1997, and (2) ASTM D1252; COD Test, 2012. Onli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The correlation between TOC and BOD 5 is recognized by the Clean Water Act and allows NPDES permit writers to accept a measurement of TOC in place of BOD 5 in permit reporting. Wastewater treatment plants recognizing this correlation have begun moving toward measuring TOC in place of BOD 5 (Assmann et al., 2017; Babatola & Xu, 2012); therefore, improved operations that reduce BOD 5 concentrations in the effluent of wastewater treatment plants will also reduce TOC concentrations. Tributaries entering Cook County also exhibited decreases in TOC concentrations, which were affected by other wastewater treatment plants outside the MWRDGC's service area, such as the Thorn Creek Basin Sanitary District (upstream of location 52), the Sanitary District of Hammond and the East Chicago Sanitary District (both upstream of location 56), the North Shore Water Reclamation District (upstream of location 13), and the Clavey Road Sewage Treatment Plant (upstream of location 32).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between TOC and BOD 5 is recognized by the Clean Water Act and allows NPDES permit writers to accept a measurement of TOC in place of BOD 5 in permit reporting. Wastewater treatment plants recognizing this correlation have begun moving toward measuring TOC in place of BOD 5 (Assmann et al., 2017; Babatola & Xu, 2012); therefore, improved operations that reduce BOD 5 concentrations in the effluent of wastewater treatment plants will also reduce TOC concentrations. Tributaries entering Cook County also exhibited decreases in TOC concentrations, which were affected by other wastewater treatment plants outside the MWRDGC's service area, such as the Thorn Creek Basin Sanitary District (upstream of location 52), the Sanitary District of Hammond and the East Chicago Sanitary District (both upstream of location 56), the North Shore Water Reclamation District (upstream of location 13), and the Clavey Road Sewage Treatment Plant (upstream of location 32).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, TOC values can be obtained in hours. Hence, for the operation of the wastewater of the airport, a TOC allows faster management (Assmann et al, 2017 ). It has been reported that both parameters are correlated (Assmann et al, 2017 ; Dubber and Gray, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the first stage of the study, the DPW was characterized by determining the COD (by the dichromate method [27]) using Hach Lange cuvette tests (LCK014, HACH, Loveland, CO, USA) in the Water Centre of the Warsaw University of Life Sciences [28] and the total organic carbon content by the supercritical oxidation method (TOC Sievers Innovox, SUEZ, Paris, France) [29]. The content of reducing sugars (per glucose) was measured spectrophotometrically at λ = 550 nm using 3,5-dinitrosalicylic acid [30].…”
Section: Dpw Chemical Characteristicsmentioning
confidence: 99%